2009
DOI: 10.1002/jbm.a.32506
|View full text |Cite
|
Sign up to set email alerts
|

Fragmin/protamine microparticles as cell carriers to enhance viability of adipose‐derived stromal cells and their subsequent effect on in vivo neovascularization

Abstract: We prepared fragmin/protamine microparticles (F/P MPs) as cell carriers to enhance cell viability. Use of material consisting of a low-molecular-weight heparin (fragmin) mixed with protamine resulted in water-insoluble microparticles (about 0.5-1 microm in diameter). In this study, we investigated the capability of F/P MPs to enhance the viabilities of human microvascular endothelial cells (HMVECs), human dermal fibroblasts (fibroblasts), and adipose tissue-derived stromal cells (ATSCs) in suspension culture. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
57
0

Year Published

2011
2011
2013
2013

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 29 publications
(58 citation statements)
references
References 31 publications
1
57
0
Order By: Relevance
“…1,9 In addition, clinical studies have revealed good results following direct injection of naked plasmid DNA encoding human VEGF or recombinant growth factors. However, their performance is limited by high cost.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…1,9 In addition, clinical studies have revealed good results following direct injection of naked plasmid DNA encoding human VEGF or recombinant growth factors. However, their performance is limited by high cost.…”
Section: Discussionmentioning
confidence: 99%
“…The F/P MPs used in this study were about 0.5 to 3 m in diameter, and the F/P MPs (200 L) subcutaneously injected into mice visually disappeared within 2 weeks. 8,9 Animal model of hindlimb ischemia. The present study used a rabbit model of hindlimb ischemia in all experiments.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, only mature vessels containing erythrocytes were counted. 6,32 Statistical analyses Statistical analysis was carried out by repeated-measures analysis of variance using the means and standard deviations for each experimental group. Scheffe's post hoc test was used for multiple comparisons, and p < 0.05 was considered statistically significant.…”
Section: Histological Analysis Of Neovascularizationmentioning
confidence: 99%